eNAMPT/TLR4 inflammatory cascade activation is a key contributor to SLE Lung vasculitis and alveolar hemorrhage - Gantsetseg Tumurkhuu; Nancy G. Casanova; Carrie L. Kempf; Duygu Ercan Laguna; Sara M. Camp; Jargalsaikhan Dagvadorj; Jin H. Song; Vivian Reyes Hernon; Cristina Travelli; Erica N. Montano; Jeong Min Yu; Mariko Ishimori; et al. (Journal of Translational Autoimmunity, 2023)
Rationale: Effective therapies to reduce the severity and high mortality of pulmonary vasculitis and diffuse alveolar hemorrhage (DAH) in patients with systemic lupus erythematosus (SLE) is a serious unmet need. We explored whether biologic neutralization of eNAMPT (extracellular nicotinamide phosphoribosyl-transferase), a novel DAMP and Toll-like receptor 4 ligand, represents a viable therapeutic strategy in lupus vasculitis. Methods: Serum was collected from SLE subjects (n = 37) for eNAMPT protein measurements. In the preclinical pristane-induced murine model of lung vasculitis/hemorrhage, C57BL/6 J mice (n = 5–10/group) were treated with PBS, IgG (1 mg/kg), or the eNAMPT-neutralizing ALT-100 mAb (1 mg/kg, IP or subcutaneously (SQ). Lung injury evaluation (Day 10) included histology/immuno-histochemistry, BAL protein/cellularity, tissue biochemistry, RNA sequencing, and plasma biomarker assessment. Results: SLE subjects showed highly significant increases in blood NAMPT mRNA expression and eNAMPT protein levels compared to healthy controls. Preclinical pristane-exposed mice studies showed significantly increased NAMPT lung tissue expression and increased plasma eNAMPT levels accompanied by marked increases in alveolar hemorrhage and lung inflammation (BAL protein, PMNs, activated monocytes). In contrast, ALT-100 mAb-treated mice showed significant attenuation of inflammatory lung injury, alveolar hemorrhage, BAL protein, tissue leukocytes, and plasma inflammatory cytokines (eNAMPT, IL-6, IL-8). Lung RNA sequencing showed pristane-induced activation of inflammatory genes/pathways including NFkB, cytokine/chemokine, IL-1β, and MMP signaling pathways, each rectified in ALT-100 mAb-treated mice. Conclusions: These findings highlight the role of eNAMPT/TLR4-mediated inflammatory signaling in the pathobiology of SLE pulmonary vasculitis and alveolar hemorrhage. Biologic neutralization of this novel DAMP appears to serve as a viable strategy to reduce the severity of SLE lung vasculitis.